The shared fish stocks conservation: revisiting the unconnected enforcement - Rachma Indriyani; Asmar Binti Abdul Rahim; Ruzita Binti Azmi (Faculty of Law, University of Muhammadiyah Malang, 2021)
“There is plenty of other fish in the sea,